MicroRNA let-7f-5p Inhibits Porcine Reproductive and Respiratory Syndrome Virus by Targeting MYH9 - Li, Na (Sci Rep, 2016)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important viral pathogens in the swine industry. Current antiviral strategies do not effectively prevent and control PRRSV. Recent reports show that microRNAs (miRNAs) play vital roles in viral infections by post transcriptionally regulating the expression of viral or host genes. Our previous research showed that non-muscle myosin heavy chain 9 (MYH9) is an essential factor for PRRSV infection. Using bioinformatic prediction and experimental verification, we demonstrate that MYH9 expression is regulated by the miRNA let-7f-5p, which binds to the MYH9 mRNA 3′UTR and may play an important role during PRRSV infection. To understand how let-7f-5p regulates PRRSV infection, we analyzed the expression pattern of both let-7f-5p and MYH9 in porcine alveolar macrophages (PAMs) after infection with either highly pathogenic PRRSV (HP-PRRSV) or classical type PRRSV (N-PRRSV) using a deep sequencing approach with quantitative real-time PCR validation. Our results showed that both HP-PRRSV and N-PRRSV infection reduced let-7f-5p expression while also inducing MYH9 expression. Furthermore, let-7f-5p significantly inhibited PRRSV replication through suppression of MYH9 expression. These findings not only provide new insights into the pathogenesis of PRRSV, but also suggest potential new antiviral strategies against PRRSV infection.